Cardioprotective effect of Solanum nigrum against doxorubicin induced cardiotoxicity-an experimental study - Varshney, Privy; Vishwakarma, Pinki; Sharma, Monica; Saini, Manish; Bhatt, Shaily; Singh, Ganesh; Saxena, K. K. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Solanum nigrum (S.nigrum) a medicinal herb is widely used in the Indian system of medicine for treatment of various ailments. The methanolic extract of S.nigrum berries had shown cardio protective and antioxidant effect. However, so far aqueous extract of S.nigrum is not scientifically evaluated for its cardio protective potential. Hence the present study was designed to find out cardio protective role of S.nigrum against doxorubicin induced cardiotoxicity. Methods: Seventy two rats were randomized into four major groups (n=6). group I received 2 ml/100 g/day normal saline p.o daily, group II received 2 ml/100 g/day of normal saline p.o daily, group III received carvedilol 30 mg/kg/day p.o daily and group IV received S.nigrum 1 g/kg/day p.o daily for test durations of 20, 30 and 40 days respectively. Doxorubicin 20 mg/kg i.p single dose was given to induce cardiotoxicity in rats of group II, III and IV respectively on last day of each experiment. Animals were sacrificed 48 hours after doxorubicin administration. Cardiac serum markers creatinine phosphokinase MB, lactate dehydrogenase, serum glutamate oxaloacetate transaminase and serum glutamate pyruvate transaminase were analysed biochemically. Histopathological changes were studied under light microscope. Results: All cardiac serum marker levels were found significantly (p<0.001) increased in doxorubicin group while S.nigrum pretreated group displayed significant (p<0.001) reduction in rise of these parameters in a time dependent manner indicating cardio protection. Histological observations further correlated the cardio protective effect of S.nigrum. Conclusions: The present study concluded that aqueous extract of S.nigrum possess cardio protective potential against doxorubicin induced cardiotoxicity.